Recent progress in magneto-optics and research on its application (Review Article): - Kojima, Norimichi; Tsushima, Kuniro (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2002)
We have investigated various kinds of magneto-optical properties for rare earthorthochromites. In RCrO3(R = Tb, Dy and Ho), from the analysis of Cr3+ exciton absorption,it was elucidated that these compounds exhibit an anomalous spin-reorientation under the magnetic field along the b axis, where the weak ferromagnetic moment of the Cr3+ spins rotatesin the ac plane perpendicular to the b axis. In these compounds, when the R3+ spin configuration is disordered, an anomalous satellite band appears in the lower energy side of the Cr3+ exciton absorption, which is associated with the breakdown of k = 0 selection rule causedby the disorder of R3+ spin configuration. In YbCrO3, various kinds of cooperative excitationssuch as Cr3+ exciton coupled with Yb3+ magnon and Cr3+-Yb3+ exciton molecule appear in the visible region, which are induced by the antisymmetric exchange interaction between the Cr3+ and Yb3+ spins. The propagation of these cooperative excitations strongly depends on the spinstructure and the external magnetic field. In ErCrO3, a photo-induced spin-reorientation takes place within 50 ms after the photo-irradiation corresponding to the 4A2g ®2Eg transition of Cr3+, and it returns to the initial spin configuration in about 400 ms. This phenomenon was detected bythe time-resolved Er3+ absorption spectra corresponding to the 4I15/2®4I9/2 transition. Finally,we briefly review the recent frontier research on application mainly developed in Japan.